22.6k views
2 votes
the vertebral needs to be eliminated to solve the system of equations below to the correct First Step negative 3x - 3y + 39 + -6x + 3 y equals -12 what is the correct answer

User Yeong
by
5.3k points

1 Answer

2 votes

Solution

For this case we have the following system of equations:

-3x -3y= 39

-6x +3y =-12

Then the correct first step would be:

Add to eliminate y

For the second part we have:

6x -8y= -94

-x +8y= 49

Then the correct first step would be:

Add to eliminate y

For the third case we have:

10x+10y =-79

10x -7y = 15

The correct first step is:

Subtract to eliminate x

For the last case we have:

-3x +2y = -15

-3x -6y =9

The correct first step is:

Subtract to eliminate x

User Donald Derek
by
5.0k points